Cognitive Bias of Hate Crime Perpetrators: How Elaboration Theory Contributes to Intergroup Violence - YuQun Jess Zhou (International Journal of Social Sciences and Public Administration, 2025)
Hate crimes, as violent acts targeting group identities, have increasingly drawn the attention of social psychology and criminology due to the cognitive mechanisms underlying them. This paper adopts the elaboration likelihood model as an analytical framework to explore the role of cognitive biases in the formation of hate crimes, aiming to reveal the complex interactive relationships among information processing pathways, emotional factors, and group identity. The study first reviews the basic characteristics of hate crimes and the theoretical development of cognitive biases, then analyses their influence on criminal motives from the perspectives of stereotypes, attribution biases, and in-group and out-group identity. Building on this theoretical framework, the study further explores how the marginal route and emotional processing biases in the Elaboration Likelihood Model solidify prejudices, weaken reflection, and thereby trigger or amplify violent behaviour. This paper argues that cognitive biases do not exist in isolation but are shaped by information processing pathways and emotional responses, which together form the perpetrator’s group hostility and tendency to justify their actions, providing psychological support for the occurrence of hate crimes. The research conclusions contribute to a deeper understanding of the cognitive causes of hate crimes and provide a theoretical basis for anti-hate education, media intervention, and social governance.